Evaluation of a radioactive rRNA:cDNA-hybridisation assay for the direct detection of Chlamydia trachomatis in urogenital specimens. Issue 5 (October 1989) - Näher, H; Niebauer, B; Hartmann, M; Söltz-Szöts, J; Petzoldt, D
Abstract : A radioactive cDNA probe complementary to chlamydial ribosomal RNA was used to detect C trachomatis in urogenital specimens. Of 37 specimens positive with cell culture 31 were confirmed by the rRNA:cDNA hybridisation test, the sensitivity being 83.8%. The specificity of the hybridisation test was 94.4%, as 186 of 197 specimens that were negative by cell culture were also negative when assessed by the hybridisation method. Given a prevalence of 15.8% the predictive values for positive and negative results were 73.8% and 96.9%, respectively. In additional experiments the possible role of microorganisms added to the specimen collection medium was investigated. However, no indication for crosshybridisation was found; at high concentrations microorganisms interfered with the test procedure.